Does it Matter? Examining the Impact of China's Vacation Policies on Domestic Tourism Demand. (August 2016) - Zhang, Chao; Singh, A. J.; Yu, Larry
With the domestic tourism market enjoying rapid expansion in the past decade, a number of significant changes in public policy have affected the institutionalization of public holidays and paid vacations in China. This article examines the impact of public policy in shaping domestic tourism development in China and estimates domestic tourism demand by applying a dynamic model using panel data. Three alternative models are applied to a panel data set made up of the ratio of domestic tourist departures in each of the 29 Chinese originating cities between 2001 and 2010. The empirical results exhibit the significant value of the lagged dependent variable on consumer decision and reveal the causal link between domestic tourism demand and consumer, trip-related and policy attributes. The findings clearly indicate that (a) China's domestic tourism market is maturing, (b) the vacation policy changes adopted in 2007 have had a significant effect in changing domestic tourism demand, and (c) domestic tourism demand has been substituted by an ever-increasing outbound tourism market. Implications are discussed for policy making and destination management.